TYPES OF TEACHER QUESTIONS AND STUDENT RESPONSES IN EFL CLASSROOM ACTIVITIES :A Case Study of Questioning in SMP in Mataram - Akmaludin, - (2009)
This study investigates the types of teacher questions, question modifications, student responses, and the ways how teacher questions facilitate EFL classroom learning. This study is conducted on the reasons that almost all classroom interactions during teaching learning process are built by questioning and it plays important roles to provide comprehensible inputs, to facilitate interaction, and to trigger students' output. This study was guided by four research questions: 1) What types of question do the teachers usually use in EFL classroom? 2) What modification techniques do the teachers employ when the questions are not understood?, 3) What sorts of responses do the questions generate from the students?, and 4) How can teacher questions facilitate language learning? This study is a qualitative case study in nature. The setting was an SMP in Mataram with two teachers and 65 students as the participants. The data were collected by non-participant observation with video recording and field notes. Analyzing data was carried out based on the field note and transcript of teacher-students' conversation gathered by video recording. It is found that the teachers use different kinds of questions in their classroom teachings. Teacher A used more referential questions, while Teacher B used more display questions. The other types of questions were also found to use such as clarification request, comprehension check, and confirmation check with less frequency. The teachers used repeating, rephrasing, decomposing, and giving additional questions to modify their questions. Student responses were categorized as verbal and non-verbal responses. The verbal responses were characterized as restricted and elaborative responses. Restricted responses were generated by display questions and elaborative responses were frequently generated by referential questions. The non-verbal responses were shown by nodding, shaking, smiling, laughing, acting, and hesitating. It is concluded that the discrepancy of using types of questions is caused by the material and approach of teaching. The use of authentic material and classroom discussion technique facilitates the teacher to use referential questions. This leads the students to provide more elaborative responses, more interactions happened and more comprehensible inputs could be provided. For this regard, broader research with more participants and longer time is recommended to carry out for further study.